Benefits of Repertorisation in Solving a Homeopathic Case - Rindasu, Ileana (Homœopathic Links, 2014)
This paper underlines the benefits of the repertorisation together with the knowledge of the Materia Medica, in order to attain the simillimum. The correct remedy is sometimes found only at the follow-up, reconsidering the information from the first consultation and/or using the information collected at the follow-ups. This paper presents a case that shows both the working method to find the simillimum and an illustrative case of the curative remedy.
Keywords: Repertorisation; Materia Medica; Simillimum; Calcarea sulphurica